2004
DOI: 10.1046/j.1600-0668.2003.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal spore transport through a building structure

Abstract: The study carried out laboratory measurements with a full-scale timber frame structure to determine penetration of inert particles with size distribution from 0.6 to 4 µm and spores of Penicillium and Cladosporium through the structure. Pressure difference over and air leakage through the structure were varied. Measurements at moderate pressure differences resulted in the penetration factors within the range of 0.05 to 0.2 for inert particles, and indicated also the penetration of fungal spores through the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Overall, spore migration may have been a function of air pressures inside the stud bays because pressure levels were similarly proportional to spore levels in both experiments. This finding is in agreement with Mosley et al (2001) and Airaksinen et al (2003) who determined that penetration factors for particles with diameters similar to those in our experiments were dependent upon pressure differences. Their analysis also showed that the bays were properly decontaminated between trials and that background spore levels did not influence spore levels inside the bays.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Overall, spore migration may have been a function of air pressures inside the stud bays because pressure levels were similarly proportional to spore levels in both experiments. This finding is in agreement with Mosley et al (2001) and Airaksinen et al (2003) who determined that penetration factors for particles with diameters similar to those in our experiments were dependent upon pressure differences. Their analysis also showed that the bays were properly decontaminated between trials and that background spore levels did not influence spore levels inside the bays.…”
Section: Discussionsupporting
confidence: 94%
“…Buttner et al (1999) demonstrated that HVAC (heating, ventilating, and air conditioning) systems in a laboratory setting have the potential to allow the movement of airborne spores into a simulated room. Airaksinen et al (2003) found that spore movement was possible through residential flooring held vertically between two chambers inside a laboratory. Fazio et al (2005) examined spore exfiltration through simulated walls to test a new penetration procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This estimation formula is similar to the one used by Airaksinen et al (2003) and is calculated from…”
Section: Discussionmentioning
confidence: 99%
“…Air sampling instruments inside the room recorded spore levels, and findings revealed that fungal spores had penetrated into the space. Airaksinen et al (2003) measured penetration factors for Penicillium spores and Cladosporium spores across an insulated residential floor held vertically between two chambers inside a laboratory. The wooden flooring contained holes that represented orifices associated with poor plumbing practices.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms for this higher prevalence include: the systems may themselves be a source of pollution from dirty filters or ducts with or without recycling of the air, while an unbalanced system, with a lower pressure in the room than outside, can bring spores and other particles from constructions and crawl space/lofts etc into the room. Experiments have shown this both in chambers and in the field (21,22). The combined effect of moulds and ventilation might be the result of a higher airflow keeping the dust whirled up by the activity of the pupils, in the breathing zone for a longer time, and thereby increasing the exposure for the occupants of the classrooms.…”
Section: Moulds In Floor Dust Mechanical Ventilation and Symptomsmentioning
confidence: 99%